Staphylococcus aureus Manganese Transport Protein C Is a Highly Conserved Cell Surface Protein That Elicits Protective Immunity Against S. aureus and Staphylococcus epidermidis - Anderson, Annaliesa S. (Oxford University Press, 2012)
Staphylococcus aureus and other staphylococci cause severe human disease, and there are currently no vaccines available. We evaluated whether manganese transport protein C (MntC), which is conserved across the staphylococcal species group, could confer protection against S. aureus and Staphylococcus epidermidis. In vivo analysis of S. aureus MntC expression revealed that expression occurs very early during the infectious cycle. Active immunization with MntC was effective at reducing the bacterial load associated with S. aureus and S. epidermidis infection in an acute murine bacteremia model. Anti-MntC monoclonal antibodies have been identified that can bind S. aureus and S. epidermidis cells and are protective in an infant rat passive protection model and induce neutrophil respiratory burst activity. This is the first description of a protein that has the potential to provide protection across the staphylococcal species group.